The A118G single nucleotide polymorphism of the μ-opioid receptor gene ( OPRM1) is associated with pressure pain sensitivity in humans - Fillingim, Roger B.; Kaplan, Lee; Staud, Roland; Ness, Timothy J.; Glover, Toni L.; Campbell, Claudia M.; Mogil, Jeffrey S.; Wallace, Margaret R. (The journal of pain, 2005)
Responses to painful stimuli are characterized by tremendous interindividual variability, and genetic factors likely account for some proportion of this variability. However, few studies have identified genetic contributions to experimental pain perception in humans. This experiment investigated whether the A118G single nucleotide polymorphism of the μ-opioid receptor gene ( OPRM1) was associated with responses to three different experimental pain modalities in a sample of 167 healthy volunteers (96 female, 71 male). Responses to thermal, mechanical, and ischemic pain were assessed in all subjects, and genotyping of OPRM1 was performed, which revealed that the rare A118G allele occurred in 24 females (25%) and 12 males (17%). Statistical analyses indicated that subjects with a rare allele had significantly higher pressure pain thresholds than those homozygous for the common allele. Also, a sex by genotype interaction emerged for heat pain ratings at 49°C, such that the rare allele was associated with lower pain ratings among men but higher pain ratings among women. These data indicate an association of a common single nucleotide polymorphism of OPRM1 with mechanical pain responses and that this genotype may be associated with heat pain perception in a sex-dependent manner. This study examines the association of the A118G SNP of OPRM1 to experimental pain sensitivity. The results indicate that the rare allele is associated with higher pressure pain thresholds. These results support previous contentions that OPRM1 may be a pain-relevant gene; however, replication of these findings is needed.